Acute effects of combined and isolated caffeine and theanine supplementation on physical and cognitive performance in competitive athletes: a randomized, double-blind, placebo-controlled crossover study - Tuncer, Selin Yildirim; Ozdenk, Serhat; Yildirim, Ulas Can; Erkan, Dilara; Sari, Cengizhan; Gundem, Mehmet Can; Sar, Halit; Yilmaz, Busra; Karakulak, Izzet; Akca, Firat (Frontiers in Nutrition, 2026)
IntroductionModern athletic performance is driven not only by physical capacity but also by rapid decision-making, attentional control, and visuomotor coordination. Evidence regarding the acute effects of caffeine (CAF), L-theanine (TEA), and their combination remains inconsistent, particularly with respect to their combined influence on physical and cognitive performance in athletic populations. This study examined the acute effects of isolated and combined CAF and TEA supplementation on maximal strength, intermittent aerobic endurance, and eye–hand coordination in competitive athletes. It was hypothesized that the combined ingestion of CAF and TEA would differentially affect physical performance and eye-hand coordination outcomes compared with isolated CAF or TEA intake.MethodsTwenty trained athletes completed four randomized, double-blind, placebo-controlled crossover conditions: CAF (3 mg·kg−1), TEA (200 mg), CAF+TEA (COM), and placebo (CON), with ≥72 h washout. Outcomes included isometric leg, back, and handgrip strength; Yo-Yo Intermittent Endurance Test Level 1 performance; and visuomotor coordination (CogniFit®). Data were analyzed using repeated-measures ANOVA with Bonferroni corrections (α = 0.05).ResultsCondition effects were found for leg strength (p = 0.004, ηp2 = 0.24) and back strength (p = 0.008, ηp2 = 0.19). In the COM condition, no additional or synergistic effect on maximal strength was observed. Additionally, no significant difference was found between the conditions in aerobic endurance, maximum isometric handgrip strength, and hand-eye coordination results. Caffeine ingestion did not differ from placebo for any strength outcome under the present conditions. Finally, acute ingestion of TEA was associated with reduced maximal isometric leg and back strength compared with CAF and CON.DiscussionFindings challenge the prevailing assumption of CAF + TEA synergy and underscore the need for task-specific interpretation of co-supplementation strategies. Future studies should evaluate dose–response interactions, habitual caffeine intake, sex-specific responses, and broader cognitive domains beyond visuomotor control. The randomized controlled trial was registered at ClinicalTrials.gov, under the registration number NCT07268573.Clinical Trial RegistrationClinicalTrials.gov, NCT07268573.